Brand managers in the pharmaceutical industry: Are they any different? - Panigyrakis, George G.; Veloutsou, Cleopatra A. (My University, 1999)
This paper examines the brand managers’ characteristics and their role in the pharmaceutical industry. It identifies the similarities and differences of that role with the role of brand managers working in the fast-moving consumer goods industry. In particular, this study investigates brand managers’ duties, by analysing their perceived involvement in activities relevant to market analysis, planning, implementation, evaluation and training and strategic and tactical decision making. The results proved that brand managers working in various sectors have a co-ordinating role and that their involvement in the strategic decision of their brands is still limited. They also indicated a dissimilarity in the perceived job responsibilities between the two industries. © 1999, MCB UP Limited
Keywords: Brands; Greece; Job descriptions; Pharmaceutical industry; Product management